Graphical user interface development for energy saving air-conditioning control system - Mohd Zaid, Mohd Zuhaili (2007)
Graphical User Interface development for energy saving air-conditioning control system means we can control the air-conditioning system by using software to reduce electricity cost. The air-conditioning system use a lot of electricity compares to other appliances and this was proved by research. We all know user sometimes did not turn off the air-conditioning either they forgot or not before leaving the room. My developed air-conditioning control software makes things easier. User can turn on or turn off the air-conditioning system by clicking one button and they also can set the time for the air-conditioning to automatically off. User can reduce their electricity bill by reduce the air-conditioning usage. This software can control up to six air-conditioning. User can control the air-conditioning by using their laptop or personal computer (PC). This software is very user friendly. The software been connected to the air-conditioning system by a circuit consist PIC 16F84 and RS232 communication module. The circuit connected to the PC using serial communication port (comm1).